Effects of Lactobacillus probiotic on growth performance and coccidiosis in broiler chickens challenged with Eimeria tenella - Shamsudin, Wan Nur Fadhilah (2019)
Avian coccidiosisis is an intestinal disease caused by several species of Eimeria (family Eimeriidae) of the phylum Apicomplexa. Probiotics had been evaluated as an alternative to anticoccidial drugs, and although the resistance of birds to coccidiosis was enhanced, but the protective effects were not always associated with an improved growth performance. Therefore, it was necessary to find probiotic species with anti-coccidiosis activity and at the same time improved broilers growth performance when challenged with E. tenella. Five out of 46 lactic acid bacteria (LAB) isolates from chicken intestine demonstrated good tolerance to acidic pH 3, 0.3% bile salts and of these, three isolates showed strong adhesion to Caco-2 cells. These three isolates also showed antagonistic activity against pathogenic E. coli (078:K80), Salmonella enterica serovar Typhimurium, C. perfringens (Type A), Salmonella enterica serovar Enteritidis, E. faecium (FM3), E. faecalis (E227). All three isolates had high inhibition zone (> 6mm) against E. coli 078:K80 and Salmonella enterica serovar Typhimurium and were susceptible to antibiotics gentamicin, kanamycin, streptomycin, tetracycline, erythromycin, clindamycin, chloramphenicol and ampicillin. These isolates were identified by using 16S rRNA sequencing technique and identified as two L. salivarius and one L. reuteri with accession number MH375403, MH375402 and MH375404, respectively. The LAB isolates were evaluated for their efficacy as anticoccidiosis alternatives in broilers challenged with E tenella. Four dietary treatments: untreated, unchallenged broilers fed basal diet (BD); treated with anti-coccidial drug (EimeriaX 12%) and challenged (ANTI); untreated and challenged (COCCID); and treated with probiotic (Lactobacilli mixture at 5x10⁸ CFU/kg) and challenged (PRO); were used in a feeding trial of 42 days with 40 chicks (Cobb 500) per treatment divided into 5 replicates. All groups, except BD, were challenged with 2x10⁴/mL of E. tenella oocysts on day 14 of broilers age. The results showed that broilers fed PRO diet had comparable body weight and feed conversion ratio (FCR) compared to BD and ANTI groups. Broilers of COCCID group had significantly lower (P<0.05) body weight and higher FCR. The lesion score was only detected in both infected chickens of PRO and COCCID groups at day 21 and was not detected at day 42. Oocyst count was significantly higher (P<0.05) in the COCCID group, compared to PRO and ANTI groups. The population of Lactobacillus spp. and Bifidobacterium spp., as well as villus and crypt depth were significantly higher (P<0.05) in the PRO group, while the populations of E. coli and C. perfringens were lower. In conclusion, the isolated LAB probiotics could improve the growth performance and alleviate the effects of coccidiosis infection when challenged with E. tenella, comparable to broilers treated with anticoccidial drug.